Oltreluce : Metafore e Forme della Luce 1960-1990 - Del Giudice, Daniele; Pierantoni, Ruggero; Pisani, Mimma; Rella, Franco; Vescovo, Marisa (Torino : Il Quadrante Edizioni, 1990)
Fontana, Lucio ; Savio, Francesco Lo ; Castellani, Enrico ; Morellet, François ; Dorazio, Piero ; Riverhead (New York) ; Colombo, Gianni ; Pistoletto, Michelangelo ; Fogliati, Piero ; Merz, Mario ; Boltanski, Christian ; Bagnoli, Marco ; Pisani, Vettor ; Mochetti, Maurizio ; Kosuth, Joseph ; Nordman, Maria ; Sonnier, Keith ; Antonakos, Stephen ; Moylan, Donna ; Rotelli, Marco Nereo ; Wanner, Franz ; Jorgensen, Anita ; Duran, Joan ; Rousse, Georges ; Busto, Andrea ; Miyajima, Tatsuo ; Ciarli, Carlo ; Othoniel, Jean-Michel ; Fukushi, Ito ; Rizzi, Renato ; Zito, Joseph ; Santachiara, Denis ; Leccia, Ange
biografie
Oltreluce : Metafore e Forme della Luce 1960-1990, Claudio Bottelo Arte, Torino, gennaio 1990 - marzo 1990
English-Italian
kunstcatalogus